Grafismo infantil: linguagem do desenhoChildrens’ Drawing: the Language of Drawing - Sell Duarte Pillotto, Silvia; Koehler Silva, Maryahn; Mognol, Letícia (Revista Linhas, 2007)
O estudo ora apresentado tem como pressuposto básico que rabiscar, desenhar e escrever não são simples atos mecânicos, ao acaso. Cada gesto e movimento têm significações simbólicas, capazes de contribuir para o desenvolvimento humano. Referimo-nos ao grafismo infantil, pesquisado, analisado e interpretado por teóricos da psicologia, da arte e da educação. Dessa forma, nosso objetivo é possibilitar o diálogo entre os vários pontos de vista de alguns dos pesquisadores dessa área, a fim de suscitar reflexões de psicólogos, educadores, pais e mães sobre o grafismo infantil como meio de linguagem da criança. PALAVRAS-CHAVE: Grafismo. Processos de criação. Criança. Simbolismo. The basic assumption of this study is that sketching, drawing and writing are not simple, mechanical random acts. Each gesture and movement has symbolic meanings that contribute to human development. We refer to childrens’ drawings, that are studied, analyzed and interpreted by theoreticians of psychology, art and education. In this way, our objective is to establish a dialog between the various points of view of some of the researchers in this field, in order to present some reflections from psychologists, educators, fathers and mothers about childrens’ drawing as a media of children’s language. KEY WORDS: Drawing. Creation processes. Child. Symbolism